Dirofilariasis Mimicking an Acute Scrotum. Issue 10 (October 2015) - Bertozzi, Mirko; Rinaldi, Victoria Elisa; Prestipino, Marco; Giovenali, Paolo; Appignani, Antonino
<x xml:space="preserve">Abstract</x> Abstract Human infections caused by Dirofilaria repens have been reported in many areas of the world. We describe a case of a 3-year-old child with an intrascrotal mass caused by D repens mimicking an acute scrotum. This represents the first case of scrotal dirofilariasis described in pediatric age with such an unusual presentation.